Strengthening Javanese Art at the Sanggar Baladewa Binjai, North Sumatra: Penguatan Kesenian Jawa di Sanggar Baladewa Binjai Sumatera Utara - Budi Agustono; Mhd. Pujiono; Heristina Dewi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
The Javanese populace is dispersed throughout Indonesia, including North Sumatra. The development of Javanese culture and art in North Sumatra paralleled the increasing number of Javanese in that region. In North Sumatra, cultural and artistic studios (sanggar) have become one of the driving forces behind the development of Javanese culture and the arts. One of them is Sanggar Baladewa in Binjai City, where Javanese arts and culture are developed and displayed. However, the sanggar faces managerial and financial difficulties. Therefore, during this community service project, efforts have been made to strengthen the Sanggar Baladewa in North Sumatra and to promote Javanese culture. This activity consists of providing sanggar members with assistance in the form of a Focus Group Discussion (FGD) over the course of three months. In addition to providing assistance, the community service team has provided sanggar members with musical instruments and accessories for use in traditional music performance activities. The lecture method, question-and-answer sessions, and demonstrations are utilized in its implementation. This Community Service has produced results in the form of services to increase public awareness of Javanese culture in North Sumatra by providing sanggar members with training to increase their creativity, innovation, and skill in the field of cultural arts.